Meningkatkan Efektivitas Mesin NC-LATHE pada Proses Piston Cup Forging dengan Menggunakan Konsep Total Productive Maintenance (Studi Kasus: PT. Hamatetsu Indonesia) - Virgi Abdul Aziz; Ade Momon (Jurnal Serambi Engineering, 2023)
AbstractTotal Productive Maintenance been implemented by PT. Hamatetsu Indonesia to boost manufacturing firms' overall effectiveness and efficiency. The objective of this research is to determine the value of the tools' effectiveness, identify its root cause, and offer suggestions for improvement. This study is a quantitative narrative based on Total Productive Maintenance (TPM) maintenance procedures designed to improve work area productivity by reducing waste and increasing reliability. In this study, interviews and direct observation were used to collect data. The obtained results indicate that the Part Piston Cup Forging production process is prone to five types of failure, namely: Reduced speed resulted in a total loss of time of 328.2, a defect in the process resulted in a total loss of time of 148.35, equipment failure resulted in a total loss of time of 11.34, setup and adjustment resulted in a total loss of time of 114.74, and idle and minor stops resulted in a total loss of time of 433.7. Additionally, there are two types of process failures identified by FMEA Processing's findings: defects that occur in the process as a result of failure effects, such as product defects that arise during the process, and defects that occur in the process as a result of failure effects, such as a decrease in machine speed. The tool on the machine, which is no longer suitable for use, and the machine's age both contributed to the process's failure.Keywords: PT. Hamatetsu Indonesia, defective products, maintenance, total productive maintenance, piston cup forging